2017
DOI: 10.1002/jcb.26042
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging and Oral Cancer Diagnosis and Therapy

Abstract: Oral cancer is known as one of relatively common type of cancer worldwide. Despite the easy access of the oral cavity to examination, oral tumors are diagnosed in more advanced stages of the disease. Imaging techniques have been recently emerged as non-invasive approaches to detect molecular and cellular changes in living cells and organisms. These techniques such as computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography (PET) could help physicians to screen patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
118
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 91 publications
0
118
0
Order By: Relevance
“…MiRNAs are small noncoding RNAs which act as epigenetic regulators in several physiological events (Fathullahzadeh et al, ; Golabchi et al, ; Keshavarzi, Sorayayi, et al, ; Keshavarzi, Darijani, et al (); Mashreghi et al, ; H. Mirzaei, Khataminfar, et al, ; H. Mirzaei et al, ; Mohammadi et al, ; Saadatpour et al, ; Salarinia et al, ). MiRNAs regulate several biological processes such as growth, development, angiogenesis, stem cell renewal, and differentiation (Banikazemi et al, ; Golabchi et al, ; Jafari et al, ; Masoudi, Mehrabian, & Mirzaei, ; H. Mirzaei, Ferns, Avan, & Mobarhan, ; H. Mirzaei, Yazdi, Salehi, & Mirzaei, ; Saeedi Borujeni et al, ; Simonian, Mosallayi, & Mirzaei, ; Tavakolizadeh et al, ).…”
Section: Mirnas As Therapeutic Candidate In Admentioning
confidence: 99%
“…MiRNAs are small noncoding RNAs which act as epigenetic regulators in several physiological events (Fathullahzadeh et al, ; Golabchi et al, ; Keshavarzi, Sorayayi, et al, ; Keshavarzi, Darijani, et al (); Mashreghi et al, ; H. Mirzaei, Khataminfar, et al, ; H. Mirzaei et al, ; Mohammadi et al, ; Saadatpour et al, ; Salarinia et al, ). MiRNAs regulate several biological processes such as growth, development, angiogenesis, stem cell renewal, and differentiation (Banikazemi et al, ; Golabchi et al, ; Jafari et al, ; Masoudi, Mehrabian, & Mirzaei, ; H. Mirzaei, Ferns, Avan, & Mobarhan, ; H. Mirzaei, Yazdi, Salehi, & Mirzaei, ; Saeedi Borujeni et al, ; Simonian, Mosallayi, & Mirzaei, ; Tavakolizadeh et al, ).…”
Section: Mirnas As Therapeutic Candidate In Admentioning
confidence: 99%
“…Cancer is one of the important diseases that are associated with various public health problems in the world . Hence, fast and suitable diagnosis platforms are needed . Several studies reported that a variety of approaches such as cell therapy, immunotherapy, gene therapy, and nanotechnology‐based methods could be applied in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that dysregulation of miRNAs can be linked to development of several disorders including stroke, cancer, diabetes, cardiovascular diseases, depression, and viral infections . Therefore, miRNAs and their targeting may be used as therapeutic, diagnostic, and prognostic markers in treatment of different diseases . These findings indicate that more exosomes enforce their oncogenic impacts through influencing miRNAs.…”
Section: Introductionmentioning
confidence: 99%